Dictionary and encyclopedia of paper and paper-making : with equivalents of the technical terms in French, German, Dutch, Italian, Spanish & Swedish - Labarre, E. J. (Amsterdam : Swets and Zeitlinger, 1952)
A detailed dictionary of technical terms with, in many cases, encyclopedic articles and descriptions, and with foreign-language equivalents. Indexes in each language
Keywords: Papermaking -- Dictionaries -- Polyglot; Dictionaries, Polyglot; Dictionaries